Adaptation and Validation of the Indonesian Version of Attitudes toward Sexuality Questionnaire in Individuals with Intellectual Disability (ASQ-ID) - Hardian, Hardian; Sumekar, Tanjung Ayu; Utari, Agustini; Winarni, Tri Indah (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: Sexuality is an integral part of adult human life, including for individuals with a disability. Even though sexuality is a fundamental right of human life, however, for a person with an intellectual disability, expressing and exploring sexuality is limited. This study aimed to determine the reliability and validity of ASQ-ID in the Indonesian language. Methods: A cross-sectional observational study designed for adaptation and validation of the Attitudes toward Sexuality Questionnaire in Intellectual Disability (ASQ-ID) of the Indonesian version was conducted in 2019. The study subjects were 617 students of Universitas Diponegoro, Indonesia. The translation process was composed of 5 steps: translation, synthesis, back translation, and semantic and conceptual analysis testing. Exploratory Factor Analysis (EFA) with principal component analysis (PCA) as a method of extraction and varimax rotation was used to identify the structure/dimensionality of observed data and identify clusters of inter-correlated variables. Pearson's r-correlation test was used to evaluate the correlation between the original and Indonesian adaptation of ASQ-ID. Cronbach-alpha was computed across all factors/sub-scales to examine the internal consistency of the adapted questionnaire. Results: Reliability analysis showed Cronbach alpha and composite reliability of items of the Indonesia version of ASQ-ID was high. EFA analysis revealed 7 emerging factors and 28 items of solutions. The items were re-group into 4 sub-scales based on the original ASQ-ID sub-scales. Conclusion: The Indonesian version of ASQ-ID has high validity and reliability in measuring the attitudes toward sexuality in individuals with ID.